The role of radiomics in dentistry and oral radiology - ., Tannishtha; Hegde, Shruthi; Babu, G. Subhas; Ajila, Vidya; Shama, B.S. (Journal of Stomatology, 2024)
Technological advances in healthcare sector have led to an increasing use of new digital techniques for diagnosis and therapeutics in medical and dental professions. Artificial intelligence (AI) is one of the most commonly discussed innovations of the present era that present the capability to transform clinical practice and research. Radiomics is an emerging field in quantitative imaging related to AI. Radiomics technology is produced as a result of combining genomic data, imaging, and pathology results. This new technology can quantify textural information through mathematical analysis from the region of interest in medical images, which the human eye cannot perceive. In oral and maxillofacial imaging, the use of cone beam computed tomography (CBCT) has been increasing that in turn encourages AI and radiomics research to assist clinicians in early diagnosis and effective treatment planning. The advent of radiomics in dentistry made it possible to improve diagnostic, prognostic, and predictive accuracy, by combining radiographic data, biological data, and clinical outcomes. Radiomics technology in dentistry is still in early phases of development. The present narrative re-view aimed to provide an up-to-date overview of the workflow and potential applications of radiomics in diagnosing and managing oral maxillofacial diseases.